Semiotics, AI, Advertising. Open Questions and Perspectives - Boero , Marianna (E|C, 2024)
The increasing spread of generative artificial intelligence (Gen-AI) technologies in advertising is significantly changing how we approach tasks, objectives, and projects, as well as how we work, communicate, and ultimately live together. This shift opens new avenues for research from a semiotic perspective, particularly regarding the relationship dynamics between the human and non-human world. The emergence of Gen-AI in advertising text production necessitates a reconsideration of classic definitions such as attribution, generativity, authorship models, text, and enunciation. Moreover, it requires an exploration of the characteristics and analytical possibilities of new emerging textual forms and narratives, with profound implications for semiotic theory. This contribution aims to delve deeper into these dimensions. Firstly, it proposes a reflection on the theoretical aspects of leveraging AI within advertising for semiotics. Secondly, it aims to classify and describe AI-driven advertising narratives, highlighting how these narratives contribute to the cultural construction of a world where intersubjective interaction and consumption models are increasingly shaped by the proliferation of new technologies.